Analisis Pragmatik Bahasa Arab: Implikasi untuk Pengajaran dan Komunikasi - Zamzamy, Muhammad; Aziz, Muhammad Tareh (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2024)
This article deals with pragmatic analysis in Arabic and its implications for teaching as well as communication. Pragmatics, as a branch of linguistics that studies the use of language in context, provides in-depth insight into how meaning is determined by communication situations. By focusing on the pragmatic elements of the Arabic language, this article aims to explain how pragmatical understanding can improve the effectiveness of Arabic teaching and improve communication skills. This research involves text analysis, interviews with linguists, and observations in real communication situations to explore the application of pragmatism in the context of education and communication. The findings suggest that a pragmatic approach can enrich learning experiences and enhance linguistic interaction.